Analysing transgenerational trauma through the lenses of contemporary texts by Anne Frank, Markus Zusak and Khaled Hosseini - Aniqua, Tasneem Habib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2023.